PERAWATAN POSTPARTUM DENGAN MINUMAN JAMU KUNYIT ASAM MENURUT PERSPEKTIF BUDAYA JAWA DI DESA BAGAN BATU KECAMATAN BAGAN SINEMBAH ROKAN HILIR RIAU TAHUN 2021 - Kartika Asdi; Suswati; Yulina Dwi Hastuty; Bebi Lovita (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
WHO describes the postpartum period as the most critical phase experienced by a mother, but it is the most neglected phase in the life of both mother and baby. Most maternal and newborn deaths occur during this period. A woman who gives birth can leave the hospital as soon as she is medically stable, a few hours after delivery, although a normal birth takes an average of one to two days to be medically stable, in contrast to a cesarean delivery which takes three or four days to recover. During the postpartum period, many postpartum mothers consume traditional herbs to support the recovery period during postpartum care. This study is a qualitative study using a phenomenological approach, the research sample was obtained through purposive sampling technique from a population consisting of postpartum mothers, from the Javanese tribe, who had or were consuming herbal ‘kunyit asam’ during the puerperium. Through the results of interviews with two types of participants, after meeting the inclusion criteria, it was found that mothers who had or are currently consuming the traditional herbs of ‘asam kunyit’ feel the same benefits, the body feels light and fit after giving birth and can also help relieve perineal tears. In line with the results of the Indonesian Basic Health Research in 2013, it is known that 49.0% of housewives use traditional ingredients to maintain their health or fitness (Ministry of Health, 2013). While the results of Indonesian Basic Health Research in 2018 stated that 55.7% of housewives used traditional health services, 48% of mothers used processed herbs and 31.8% used herbs that were prepared by themselves.